Effects of land use on water quality at different spatial scales in the middle reaches of Huaihe River. Issue 1 (4th February 2023) - Mu, Ming; Gao, Liangmin; Zhang, Haiqiang; Ge, Juan; Zhang, Zhen; Qiu, Yuhui; Zhao, Xinglan
Abstract: The impact of land use on water quality is spatially scale-dependent. Exploring the relationship between land use pattern and river water quality provides an important basis for water quality safety and land planning. This study explores the effect of land use patterns on surface water quality using land use data and water quality data of 16 sampling points in the middle reach of the Huai River. It investigates the water quality status of the middle reach of the Huai River and the relationship between land use patterns and water quality indices at 100, 500, and 1000 m and watershed scales utilising Spearman correlation, redundancy analysis (RDA), and multiple linear regression analysis. Multiple linear regression analysis showed that the water pollutants in the middle reach of the Huai River are mainly total nitrogen (TN) and total phosphorus (TP). Redundancy analysis (RDA) indicated that the impact of land use patterns on water quality is significant on watershed scales. Spearman correlation indicated that water quality and land use showed significant correlation differences, the building land was positively correlated with TP, TN and NH3 -N, the cultivated land was positively correlated with TN, and the grassland was negatively correlated with TP and NH3 -N. This studies have revealed that building land acts as a 'source' of pollutants, grassland purifies the load of TP and NH3 -N, and forest land has the effect of interception and deposition of pollutants. The results can provide important information for land use planning and water quality protection measures at multiple spatial scales.